Greatness takes practice: On practice theory’s relevance to “Great Strategy” - Whittington, R (INFORMS, 2017)
This paper draws on the Practice theory of Pierre Bourdieu, Michel de Certeau, Michel Foucault, Anthony Giddens and Alasdair MacIntyre to explore the origins of great strategies. Despite its’ naturally rather modest approach to social life, Practice theory does speak to the question of greatness. In particular, I shall derive five principles capable of building great strategies: value the ordinary, see past markets, embrace diversity, allow for the bottom-up and accept different forms of greatness. The paper proposes ways in which Strategy as Practice researchers can be more ambitious with regard to issues of performance, particularly through ethnographic case studies of ‘great’ companies and of companies with different criteria of performance. The paper also identifies parallel research traditions with which Strategy as Practice researchers might work more closely, for instance those associated with Design thinking, non-market strategy and institutional entrepreneurship and innovation. It also identifies opportunities and risks in working with the psychological traditions of Microfoundational and Behavioral Strategy.